Nosocomial Multi-Drug-Resistant Acinetobacter Infections - Clinical Findings, Risk Factors and Demographic Characteristics (Bangladesh Journal of Medical Microbiology, 2009)
Recently, Acinetobacter emerged as an important pathogen and the rate of isolation has increased since the last two decades worldwide. Objectives of the present study were to see the incidence of Acinetobacter infection at a tertiary care hospital at Kashmir, India, demographic features of the infections, species identification and antibiotic sensitivity and resistance pattern of the isolates. The clinical samples submitted to Microbiology laboratory at SKIMS over a period of 2 years (June, 2001 to June, 2003) were investigated. Identification, speciation and antibiotyping were performed for the isolates of Acinetobacter recovered from clinical samples including urine, pus, sputum, blood, CSF and other body fluids. Clinical and demographic characteristics were studied retrospectively. Out of a total of 5352 infected samples, 258 (4.8%) were found to be due to Acinetobacter. The organism was responsible for 76 (39.64%) cases of urinary tract infection and 38 (29.45%) cases of wound infection and was most prevalent in the intensive care unit (29.84%). A. baumannii was the most predominant species. Prolong hospital stay, Mechanical ventilation and Intensive Care Units were found to be potential risk factors. High level of resistance was recorded for Ampicillin (86.3%), Cefazolin (93.2%) Gentamicin (61.5%), Cefotaxime (65.8%), Ceftriaxone (61.5%) and Ciprofloxacin (69.2%). Although no specific pattern during antibiotyping was observed, but most of them were multi-drug resistant. Nosocomial infections by multi-drug-resistant Acinetobacter have emerged as an increasing problem especially in the intensive care units of the hospital. The analysis of risk factors and susceptibility pattern will be useful in understanding epidemiology of this organism in a hospital setup. Key words: Acinetobacter, Nosocomial infection, Antibiotyping, Multi-drug resistant   doi: 10.3329/bjmm.v3i1.2969 Bangladesh J Med Microbiol 2009; 03 (01): 34-38